2022
DOI: 10.1126/sciadv.abp9471
|View full text |Cite
|
Sign up to set email alerts
|

Two cooperative binding sites sensitize PI(4,5)P 2 recognition by the tubby domain

Abstract: Phosphoinositides (PIs) are lipid signaling molecules that operate by recruiting proteins to cellular membranes via PI recognition domains. The dominant PI of the plasma membrane is phosphatidylinositol 4,5-bisphosphate [PI(4,5)P 2 ]. One of only two PI(4,5)P 2 recognition domains characterized in detail is the tubby domain. It is essential for targeting proteins into cilia involving reversible membrane association. However, the PI(4,5)P 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 66 publications
3
19
0
Order By: Relevance
“…Figure 3A shows the PCLδ1 PH domain with a PI(4,5)P2 lipid in its crystal structure binding pocket embedded in a POPC bilayer. Unbiased MD simulations starting from the membrane-bound structure confirm the high affinity of the PLCδ1 PH domain to a single PI(4,5)P2 lipid (Figure S2) which has also been shown previously based on atomistic as well as CG simulations 40,49,65,67,68 . We used three different structural bias models.…”
Section: Case Studies: Showing the Advantages Of Gōmartinisupporting
confidence: 84%
See 1 more Smart Citation
“…Figure 3A shows the PCLδ1 PH domain with a PI(4,5)P2 lipid in its crystal structure binding pocket embedded in a POPC bilayer. Unbiased MD simulations starting from the membrane-bound structure confirm the high affinity of the PLCδ1 PH domain to a single PI(4,5)P2 lipid (Figure S2) which has also been shown previously based on atomistic as well as CG simulations 40,49,65,67,68 . We used three different structural bias models.…”
Section: Case Studies: Showing the Advantages Of Gōmartinisupporting
confidence: 84%
“…Moreover, the fully reparameterized Martini 3 model for proteins is presented, pointing to which improvements in the model may enable more accurate predictions of protein packing and protein interactions 38,39 . The GōMartini implementation together with Martini 3 has already shown that it can capture subtle changes in protein dynamics caused by interactions with membranes 40 , single point mutations 41 and mechanostability. 42 We also show how the virtual-site implementation can be used to implement an environmental bias to correct recently described inaccuracies of the model, such as underestimated dimensions of intrinsically disordered proteins (IDPs) 43,44 and low hydrophobicity of certain amphiphilic small peptides.…”
Section: Introductionmentioning
confidence: 99%
“…We surveyed the myofiber localization of eight selective biosensors available for five of the seven different PIPs, including PI(3)P, PI(4)P, PI(3,4)P 2 , PI(4,5)P 2 and PI(3,4,5)P 3 . Only the PI(4)P indicator, P4M (Brombacher et al, 2009, Hammond et al, 2014, Liu et al, 2018), and the two PI(4,5)P 2 indicators, GFP-tagged PH-PLC8 and Tubby-C (Santagata et al, 2001, Stauffer et al, 1998, Thallmair et al, 2022, Varnai and Balla, 1998), were found to localize at the T-tubule network in larval body wall muscles ( Supplemental Figure S2B ). In wildtype conditions, both PI(4)P and PI(4,5)P 2 co-localized with Dlg1, as well as with each other, along T-tubule membranes ( Figure 2A-2E ).…”
Section: Resultsmentioning
confidence: 99%
“…Martini has been heavily used to study specific protein–lipid interactions, particularly the protein’s lipid “fingerprint”, i.e., the unique local lipid environment around a protein when inserted in a complex membrane . Some examples of this are the extensive work done on a variety of G protein-coupled receptors (GPCRs), several pores and transmembrane channels, and peripheral membrane proteins, , among many others. …”
Section: Main Cg Protein Model Applicationsmentioning
confidence: 99%